Incidência microbiana e medidas preventivas de contaminação em superfícies de um centro cirúrgico - Bardaquim, Vanessa Augusto (2012)
The composition and concentration of microorganisms are extremely important components to demonstrate the level of hygiene in hospital operating rooms. The information from these strategies can be developed to maintain a biologically safe hospital environment by eliminating the focus of contact and transmission, and thus preventing nosocomial infections that cause a considerable increase in length of hospitalization, morbidity and mortality and thus helping to increase hospital costs, delays the recovery of patients and higher public spending. Another factor is the association of bully resistant microorganisms in hospital infections. Given the importance of the theme of contamination NI Microbial resistance and because there are few studies in Brazil where it may be noted the degree of microbial contamination on surfaces (table medication, surgical table, marble countertops and air conditioning grilles) of an operating room of a medium-sized hospital, the present study was conducted to quantify and identify bacteria and fungi these surfaces and assess the resistance profile to some antimicrobials of bacterial isolates. Samples were collected with the aid of a swab soaked in sterile peptone water and rubbed into quadrants of 20 cm2 surface under study. Hafnia alvei was detected (2,9%), Pseudomonas spp. (4,3%), Shigella spp. (4,3%), Staphylococcus aureus (5,7%), Staphylococcus coagulase-negative (5,71%), Staphylococcus spp. (50,0%) e Bacillus spp (12,9%). All strains of S. aureus showed sensitivity and resistance to Penicillin G, Amoxicillin and Oxacilina. Given this information from contamination of the surfaces studied, presents measures to minimize these contaminants in order to provide or improve the welfare of the occupants of such environments with the implementation of practices and standards based upon current legislation, minimizing the problems that may occur with the health of both employees and users of outpatient services and hospital.